Democratic In-Depth Analysis of Mining Extractivism in Latin America - Martínez Espinoza, Manuel Ignacio (Geopolítica(s). Revista de estudios sobre espacio y poder, 2018)
The article analyses mining extractivism in Latin America. It makes two major contributions. First, it sets forth an explicative model of mining extractivism in Latin America based on four cross-regional patterns: the emergence of transnational mining, institutional assistance, land-grabbing and constant unrest. Secondly, the article discusses the model of mining extractivism drawing on a plural and antagonist reading of democracy. The latter is critical with the liberal-representative-procedural dimension of mining extractivism and has paid little attention to opponents to the model. The article concludes that, in spite of the exceptions to the model, mining extractivism perpetuates Latin America’s primary-sector and export-oriented economic basis, her external dependence and coloniality, while nonetheless shows that democracy’s constituent power sets up limits to this mining model.